Rumen degradable nitrogen supplement requirement for nutrient utilization from finger millet (Eleucine coracana) straw by crossbred cattle - PRASAD, C S; SAMPATH, K T; SHIVARAMAIAH, M T; SHIVAKUMAR, N; SUBBA RAO, A (The Indian Journal of Animal Sciences, 2013)
Finger millet straw (Eleucine coracana) supplemented with groundnut-cake (GNC) and cotton seed-cake (CSC) at 15 and 30 g level of rumen degradable nitrogen (RDN) per kg digestible organic matter (DDM) was fed to 30 crossbred heifers distributed equally under each regimen. The dry-matter intake of straw (DMIS) did not differ significantly under the 2 cake sources and nitrogen levels than that under the unsupplemented straw grouP. But the total DMI was significantly higher (p